Student modeling for learning of object-oriented programming in e-learning environment - Abdullah Mohd Zin; Sufian Idris; Nantha Kumar Subramaniam (2006)

(untitled)
E-Learning environment offers some interesting benefits over traditional learning environments. Students’ learning in e-learning environment can be independent of distance, time, computing platform and classroom size. E-Learning also provides diversity and completeness of knowledge. In an e-learning environment, students learn by going through learning materials provided through a web-based learning management system. However, most of the learning management systems are nothing more than a network of statically linked hypertext pages. To better support the learning activities of a large number of students with different learning styles, and diverse background and learning goals, there is a need for a more adaptive and intelligence learning management system. To achieve this objective, this system must be able to provide a more personalised approach for learners. This is particularly important in the learning of programming, since different learner would normally face with different problem. The most important component for developing a more adaptive and intelligent learning management system is the students model. The purpose of this paper is to investigate and then to propose a students model for learning of object-oriented programming in an e-learning environment. The development of this model is based on our experience in handling courses on object-oriented programming at Open University Malaysia (OUM) over more than four years. (Authors' abstract)